The overnight interbank market: Evidence from the G-7 and the euro zone - Alessandro Prati; Leonardo Bartolini; Giuseppe Bertola (Federal Reserve Bank of New York, 2001)
This study of the major industrial countries' interbank markets for overnight loans links the behavior of very short-term interest rates to the operating procedures of the countries' central banks. Previous studies have focused on key features of the U.S. federal funds rate's behavior. We find that many of these features are not robust to changes in institutional details and in the style of central bank intervention, along both cross-sectional and time-series dimensions of our data. Our results suggest that the empirical features of the day-to-day behavior of short-term interest rates are more strongly influenced by institutional arrangements than by extensively researched market frictions.
Keywords: E43; E52; E58; 330; interest rates; reserve requirements; central bank procedures; Geldmarkt; Zins; Zinsstruktur; Währungsreserven; Zentralbank; Europäische Wirtschafts- und Währungsunion; G-7-Staaten